Ozone Risk Assessment and Mapping in the Alps Based on Data from Passive Samplers - Cristina Mazzali; Elisabetta Angelino; Giacomo Gerosa; Antonio Ballarin-Denti (The Scientific World Journal)
Passive samplers (diffusion tubes with organic reagent, produced by Passam of Switzerland) were used in a sampling campaign for the detection of weekly mean ozone concentrations in 15 sites over a domain of 80 x 40 km on the southern side of the European Alps from May to August 1998. The area is characterized by vast natural terrain of complex topography, with conifer and broadleaf forests. It is difficult to access and monitor air quality there with continuous analysers. By applying geostatistical techniques (ordinary kriging), and correcting the interpolated ozone concentrations according to the altitude of each single grid cell (2 x 2 km), maps of weekly ozone concentrations were produced. The weekly ozone data were used to assess daily and hourly data by means of an iterative procedure based on a functional dependence of ozone concentrations both on altitude and on the time of day. This allowed the estimation of values with an exposure index such as AOT40 (accumulated exposure over the threshold of 40 ppb) in all 800 cells of the domain. This also allowed the mapping of risk assessment related to the effects of ozone on the regional forest vegetation. Results obtained show values that exceed the exposure standards adopted in the Kuopio protocol (1996). Excess exposure values also match values calculated over a wider territorial domain by using hourly data on ozone concentration derived from continuous automatic analysers.